Business or pleasure - Solomon, Rachel Lynn (Berkley Romance, 2023)
"A ghostwriter and a struggling actor help each other on the page and in the bedroom in this steamy romantic comedy from the New York Times bestselling author of The Ex Talk. Chandler Cohen has never felt more like the ghost in 'ghostwriter' until she attends a signing for a book she wrote--and the author doesn't even recognize her. The evening turns more promising when she meets a charming man at the bar and immediately connects with him. But when all their sexual tension culminates in a spectacularly awkward hookup, she decides this is one night better off forgotten. Unfortunately, that's easier said than done. Her next project is ghostwriting a memoir for Finn Walsh, a C-list actor best known for playing a lovable nerd on a cult classic werewolf show who now makes a living appearing at fan conventions across the country. But Chandler knows him better from their one-night stand of hilarious mishaps. Chandler's determined to keep their partnership as professional as possible, but when she admits to Finn their night together wasn't as mind-blowing as he thought it was, he's distraught. He intrigues her enough that they strike a deal: when they're not working on his book, Chandler will school Finn in the art of satisfaction. As they grow closer both in and out of the bedroom, they must figure out which is more important, business or pleasure--or if there's a way for them to have both"--